The management of suspected scaphoid fractures in English hospitals: a national survey. (June 2016) - Smith, Jason E.; House, Robyn H.; Gallagher, Jessica; Phillips, Alistair
Abstract : Background: Wrist injuries are common, and there is often diagnostic uncertainty following normal initial radiographs when there is ongoing clinical suspicion of a scaphoid fracture. The aims of this study were to define the problem in our hospital, and to identify current practice relating to the management of patients with clinically suspected scaphoid injury across hospitals in England. Methods: A retrospective review was undertaken of all patients presenting to our Emergency Department with a wrist injury, over a 12-month period. A cross-sectional survey of all hospitals in NHS England was then undertaken, using a web-based questionnaire. The results of the survey were analysed in Microsoft Excel to provide descriptive data only. Results: Of 2367 patients presenting to our Emergency Department with a wrist injury, 420 (17.7%) were followed up due to ongoing clinical suspicion of a scaphoid injury. From the 141 acute hospital Trusts in NHS England, survey responses were received from 116 (82% response rate). Symptomatic patients undergo repeat radiograph in 68.0% of hospitals before second line imaging. This is performed using MRI in 63.9%, computed tomography in 27.0% or isotope bone scan in 9.0%. Secondary imaging is carried out between 10 days and 4 weeks following the initial injury in 86.8% of trusts. Conclusion: This is still considerable variability in the way these patients are managed in England. Further work needs to be undertaken to establish the most appropriate way to manage patients with wrist injuries with ongoing clinical suspicion of scaphoid fracture.